We mean business: Malaysian finance minister says reforms will continue. - Crovitz, L. Gordon; Chanda, Nayan; Silverman, Gary (Far Eastern Economic Review, 1995)
In an interview, Malaysian deputy prime minister and finance minister Datuk Seri Anwar Ibrahim discusses his visit to Hong Kong to tout Malaysian financial centers. Anwar replies to questions regarding the reception he received in Hong Kong, the greatest obstacles to attracting fund managers to Malaysia, the effect of scripless trading on the Singapore exchange, whether he will open the Employees Provident Fund to domestic and foreign managers and the Malaysian retail market to foreign fund managers, whether foreign brokers will be given licenses to trade in Malaysia, and whether he sees any opportunities in the return of Hong Kong to Chinese rule in 1997.